Effect of combined microwave-ultrasonic pretreatment of real mixed sludge on the enhancement of anaerobic digester performance - Yeneneh, Anteneh; Kayaalp, A.; Sen, Tushar; Ang, Ming (Springer International Publishing, 2015)
The anaerobic biodegradability of combined microwave-ultrasonic pretreated thickened excess activated sludge (PTEAS) mixed with raw primary sludge (PS) was investigated in this study. The pretreatment resulted in the enhancement of mesophilic anaerobic digester performance which in turn improved biogas production capacity and quality, total and volatile solid reduction, dewaterability, protein solubilisation and significant reduction of pathogens to produce class A biosolid. This study presented the results of two continuously stirred mesophilic anaerobic digesters charged with various proportions of a mixture of PTEAS and PS similar to the large-scale industrial practice. Digester 1 was charged with 75 % PTEAS and 25 % PS, while digester 2 was fed with 25 % PTEAS and 75 % PS. The methane production was 122 mL CH4/g total chemical oxygen demand for digester 2 after 20 days of anaerobic digestion. This amount further increased for both digesters with digestion time. The biogas quality in terms of methane to carbondioxide ratio (CH4/CO2) was significantly improved for digester 1 compared with digester 2 after 20 days of digestion. Volatile solid reduction of 76 and 57 % was achieved for digester 1 and digester 2 respectively after the same 20 days of digestion. The CH4/CO2 ratio reached 2.2:1 and 1.1:1 after 20 days of digestion for digester 1 and digester 2, respectively. Higher percentage of PTEAS increases the digestion kinetics, the methane production capacity and the biogas quality. Furthermore, total coliform reduction of 84 and 44 % was achieved for digester 1 and digester 2 respectively after 22 days of digestion. Hydrolysis rate and biochemical methane production were improved for both digesters based on the results of Gompertz kinetic model and the hydrolysis rate constants as determined by model fitting of the experimental data.